Proposed guidelines for the development of an audiobook collection for the Quezon City Public Library - Aman, Theo Rafael S. (School of Library and Information Studies, University of the Philippines Diliman, 2014)
Audiobooks have been available to the public since the early 1960s, but it has yet to gain traction in the Philippines. Audiobooks started out as a way for the visually-impaired to acquire literary entertainment, but ove time sighted people came to enjoy audiobooks as well, so much so that even university libraries in the US have started acquiring audiobooks due to demand. Furthermore, with the ever-reducing price of portable media devices (e.g. smartphones, tablets, MP3 players), listening to audiobooks has become a cinch because audiobooks nowadays are being sold either in CD format or direct download from the vendor's website.